Editorial [to] Themed issue on sustainability in energy and buildings, part 2 - Calautit, John Kaiser (Institution of Civil Engineers, 2017)
This issue of Engineering Sustainability is the second part of our themed issue on ‘Sustainability and energy in buildings’, which includes the selected papers from the proceedings of the seventh International Conference on Sustainability and Energy in Buildings 2015 (SEB15). Annually, the conference brings together researchers and government and industry professionals to discuss the future of energy in buildings, neighbourhoods and cities from a theoretical, practical, implementation and simulation perspective. Part one of the issue (Calautit, 2017) explored emerging research topics in the areas of energy and buildings, including big data, renewable energy integration, energy performance gap, advanced materials and technologies in building construction, hybrid energy systems and smart cities. Part two focuses on topical issues in engineering sustainability including embodied energy and emissions, energy modelling, external wall insulation, in-construction testing methods and energy sources in non-interconnected regions.